THE DOCTRINAL EVOLUTION OF CIVIL-MILITARY COOPERATION IN UKRAINE: ITS POLITICAL AND LEGAL ESSENCE, INTERNATIONAL EXPERIENCE, AND TRANSFORMATION IN THE CONTEXT OF THE RUSSO-UKRAINIAN WAR - Obodianskyi, Yaroslav; Kalynovskyi, Roman (Public Management and Policy, 2026)
Following the end of the Cold War and the subsequent escalation of regional conflicts in Europe and the Middle East, the limitations of the traditional political and legal framework of international security became increasingly evident. At the same time, classical military means and methods, primarily oriented toward ensuring international and national security as well as state defense within established security paradigms, gradually proved insufficient in the face of new types of threats. The contemporary security system is largely shaped by hybrid and asymmetric challenges, which necessitate a reconsideration of the role of the armed forces, public authorities, civilian institutions, and society as a whole within an integrated system of ensuring national security and defense. Under these conditions, transformation affects not only national security models but also collective security structures and established treaty-based platforms for international cooperation, including NATO, the United Nations, the European Union, the OSCE, and others. In view of this, one may predict a further increase in the role of regional structures – political, military, and economic – which will increasingly act not merely as auxiliary elements of the global security architecture, but also as autonomous centers of decision-making, resource coordination, and crisis response. In the context of the Russian-Ukrainian war and Ukraine’s simultaneous strategic course toward Euro-Atlantic integration, the military-political leadership of the state is increasingly emphasizing the importance of public trust, value-based solidarity, moral authority, and international support as intangible factors of defense capability. At the same time, these factors cannot remain solely at the level of declarative guidelines, since under wartime conditions they require conversion into concrete material, managerial, and strategic outcomes. It is precisely in this context that civil-military cooperation bodies were institutionalized within the Armed Forces of Ukraine. These bodies have undergone an evolutionary path from a relatively peripheral structure with predominantly auxiliary functions to an important component of the management mechanism that combines military rationality with the logic of humanitarian, social, and political-legal governance. This evolution is reflected not only in the practical experience of the functioning of civil-military cooperation, but also in doctrinal normative legal acts, which have gradually reinterpreted the place and role of civil-military cooperation within the state defense system. Accordingly, the change in doctrinal approaches to civil-military cooperation demonstrates a broader transformation in the views of the military-political leadership regarding the interaction among the defense forces, the civilian population, public authorities, local self-government bodies, and international partners under conditions of the Russian Federation’s prolonged armed aggression against Ukraine.